Levantamento das espécies de trepadeiras de um fragmento de floresta estacional semidecidual, em Fênix, Paraná - Gois, Sara Belini de (2015)
The knowledge regarding vine plants in the state of Paraná is still scarce. Typical members of the seasonal semideciduous forests, they are plants with acknowledged significance for the structural, floristic and functional aspects of the landscape. This study had, as intent, the floristic assessment of species of vines in the private reserve of “Patrimônio Natural Agro Mercantil Vila Rica Ltda,” as well as its dispersion characteristics and creeper habits. On a weekly basis, from March to December of 2014, samples were collected. The dispersion characteristics and classification of the ascending mechanism followed the methodologies of field observation, queries to the records from “HCF Herbarium,” morphological analysis (flower, fruit and seed,) and literature review. Inside the natural reserve of “Patrimônio Natural Agro Mercantil Vila Rica Ltda” were registered 21 vine species, distributed among 14 botanical families. In terms of species, the family with greatest variety was Bignoniaceae, with five recorded species; followed by Malpighiaceae, Nyctaginaceae, and Sapindaceae, with two species, respectively. Together, they amount for 52,4% of the richness in the reserve. Considering the dispersion characteristics, the most representative are the 10 anemochoric species, accounting for 47,7% of the total; followed by eight zoochorous and three autochorics. The predominant creeper habit was the prehensile (10 species,) followed by the scandents (eight species) and volubles (three species). The Bignoniaceae family presented exclusively prehensile species, and Nyctaginaceae only scandent ones. Continuity of the study concerning vines in this conservation unity is advised.